An international comparison of rice consumption behaviours and greenhouse gas emissions from rice production. (20th January 2018) - Maraseni, Tek Narayan; Deo, Ravinesh C.; Qu, Jiansheng; Gentle, Popular; Neupane, Prem Raj
Abstract: Rice is a staple food for over half the global population and is mostly produced by smallholders. Rice cultivation at global level is responsible for over 10% of global agricultural greenhouse gas (GHG) emissions and about 1.3%–1.8% of the anthropogenic GHG emissions. Taking time series data from the World Bank, Food and Agriculture Organisation, International Rice Research Institute and United States Department of Agriculture, this study aims to compare the trends and magnitudes of rice yield, per capita rice consumption and its relationships with per capita income and life expectancy, as well as CH4 and N2 O emissions from rice farming among the eight different countries (China, India, Vietnam, Thailand, the Philippines, Myanmar, Bangladesh and Indonesia) which, collectively, account for about 82.05% of the global rice production and 78.23% of the global rice consumption. Moreover, agricultural practices as a whole in these eight countries is responsible for 35% of global agricultural emissions. Over the 54 year period of study from 1961 to 2014, rice yield increased significantly in all countries; however, the current pace is not sufficient to meet the increasing demands. Similarly, results suggest that the generalisation of rice consumption behaviour—as normal or inferior goods—is misleading and is largely influenced by the culture, norms, values and beliefs of a given country. Although the absolute amounts of GHG emissions from rice cultivation has increased in all countries during the study period, the corresponding emission intensities have declined sharply, mainly due to the rapid increase in yield. Among the eight countries, China and Vietnam's performance was better in terms of their increased yield, decreasing rates of emissions intensity and a lower water footprint whilst Thailand's performance was poorest. The differences between the different countries and practices which enable more rice to be produced with less water, energy and land are also discussed. Highlights: Compared the trends and magnitudes of rice yield and related greenhouse gas emissions. Generalisation of rice consumption behaviour is misleading. Absolute amounts of emissions increased but emissions intensities declined sharply. China's performance stands out whilst Thailand's performance was poorest. Practices which enable more rice to be produced with less resources are highlighted.